DEVELOPMENT OF SURFACE FACILITIES DESIGN PRINCIPAL IN GAS CONDENSATE RESERVOIR AS A FUNCTION OF RESERVOIR PROPERTIES VARIATION DISTRIBUTION - ASTELINA (NIM : 22208029), SARAH
This study was conducted in order to know the effect of changing reservoir properties distribution, in term of porosity and permeability to surface facilities design. Statistic method was used to distribute reservoir properties by changing standard deviation σ value of porosity normal distribution and p value of permeability p-normal distribution. PVT analysis and History Matching for the model was done first to get valid model, then followed by reservoir performance forecast with sensitivities of varying σ porosity distribution and p permeability distribution for each layer. Surface facilities design was adjusted with reservoir simulation result for each sensitivities. The result showed that change in porosity distribution which was affected by standard deviation σ value variation and p value variation in permeabilitydistribution contribute to compressor, chiller, cooler, and pump in designing surface facilities for gas and condensate processing. Every σ (standard deviation of porosity distribution) set at 0.02 in every p value permeability distribution set at 0.5 affect surface facilities design, such as : compressor 1 power in gas processing unit at 2097 Ã‚Â– 11,819 hp, compressor 2 power in gas processing unit at 1994 Ã‚Â– 11,242 hp, chiller duty in gas processing unit at 5,769,964 Ã‚Â– 32,539,029 Btu/hr, cooler 2 duty in gas processing unit at 4,843,421 Ã‚Â– 27,300,865 Btu/hr, power pump in condensate processing unit at 0.901 Ã‚Â– 5.82 hp, and cooler 1 duty in condensate processing unit at 25,770 Ã‚Â– 120,412 Btu/hr. Decreasing standard deviation σ at 0.02 in every p value permeability distribution set at 0.5 have small effect in surface facilities design, such as : compressor 1 power in gas processing unit at 2097 hp, compressor 2 power in gas processing unit at 1994 hp, chiller duty in gas processing unit at 5,769,964 Btu/hr, cooler 2 duty in gas processing unit at 4,843,421 Btu/hr, power pump in condensate processing unit at 0.901 hp and cooler 1 duty in condensate processing unit at 25,770 Btu/hr. Increasing of standard deviation σ at 0.1 in every p value permeability distribution set at 0.5 have big effect in surface facilities design, such as : compressor 1 power in gas processing unit at 11,819 hp, compressor 2 power in gas processing unit at 11,242 hp, chiller duty in gas processing unit at 32,539,029 Btu/hr, cooler 2 duty in gas processing unit at 27,300,865 Btu/hr, power pump in condensate processing unit at 5.82 hp and cooler 1 duty in condensate processing unit at 120,412 Btu/hr. Sharp increase to line formed from σ = 0.02 to σ = 0.04 for every p permeability distribution, this is caused by the smaller of standard deviation σ value of porosity distribution, the higher porosity distribution uniform, and vice versa.